2012
DOI: 10.1016/j.cell.2012.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Innate Immunity Is Required for Efficient Nuclear Reprogramming

Abstract: Retroviral overexpression of reprogramming factors (Oct4, Sox2, Klf4, c-Myc) generates induced pluripotent stem cells (iPSCs). However, the integration of foreign DNA could induce genomic dysregulation. Cell-permeant proteins (CPPs) could overcome this limitation. To date this approach has proved exceedingly inefficient. We discovered a striking difference in the pattern of gene expression induced by viral versus CPP-based delivery of the reprogramming factors, suggesting that a signaling pathway required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
313
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(333 citation statements)
references
References 44 publications
17
313
1
2
Order By: Relevance
“…69 In addition, it was recently shown that TLR3 stimulation on somatic cells caused global changes in the expression of epigenetic modifiers leading to enhanced chromatin remodeling, nuclear reprogramming, cell plasticity, pluripotentiality, transdifferentiation and even malignant transformation. 70 In line with these data, experiments in breast cancer cells put in evidence that NF-kB and b-catenin signaling downstream of TLR3 promoted the enrichment of a subset of cells with CSC phenotype. 71 Similarly, in the haematopoietic stem/progenitor cell (HSPC) compartment, chronic Type-I-IFN stimulation resulted in HSPC loss of quiescence and dysfunction.…”
Section: Cancer-intrinsic Effects Of Type-i-ifnssupporting
confidence: 55%
“…69 In addition, it was recently shown that TLR3 stimulation on somatic cells caused global changes in the expression of epigenetic modifiers leading to enhanced chromatin remodeling, nuclear reprogramming, cell plasticity, pluripotentiality, transdifferentiation and even malignant transformation. 70 In line with these data, experiments in breast cancer cells put in evidence that NF-kB and b-catenin signaling downstream of TLR3 promoted the enrichment of a subset of cells with CSC phenotype. 71 Similarly, in the haematopoietic stem/progenitor cell (HSPC) compartment, chronic Type-I-IFN stimulation resulted in HSPC loss of quiescence and dysfunction.…”
Section: Cancer-intrinsic Effects Of Type-i-ifnssupporting
confidence: 55%
“…Stimulation of TLR3 seems to affect the expression and/or distribution of epigenetic modifiers promoting an open chromatin configuration and thus nuclear reprogramming. Although these findings recommend stimulation of the innate immune system for efficient mRNA-based iPSC generation, the authors also note that the level of TLR3 should be balanced, as further stimulation can cause cell death [144].…”
Section: Current State Of Non-immunotherapy Related Mrna Applicationsmentioning
confidence: 99%
“…Therefore, iPSCs must be screened to select free cells for further applications (Gonzalez et al, 2009). To date, the safest technique of iPSC production is induction of pluripotency via mRNA (Warren et al, 2012;Yoshioka et al, 2013) or protein (Kim et al, 2009;Lee et al, 2012). These iPSCs are called "clean" iPSCs.…”
Section: Cell Fate and Reprogrammingmentioning
confidence: 99%